Restoring watersheds project by project: trends in Chesapeake Bay tributary restoration. Issue 5 (1st June 2005) - Hassett, Brooke; Palmer, Margaret; Bernhardt, Emily; Smith, Sean; Carr, Jamie; Hart, David
Abstract : Restoration of aquatic ecosystems is a high priority regionally and globally, yet only recently have such efforts adopted holistic approaches that include the restoration of streams and rivers flowing to coastal areas. As the largest estuary in the US, the Chesapeake Bay has been the focus of one of the most high‐profile restoration programs ever undertaken in North America. While the primary emphasis has been on tidal waters, freshwater tributary clean‐up strategies have recently been developed. We have compiled the first comprehensive database of over 4700 existing river and stream restoration projects in the Chesapeake Bay Watershed (CBW) to examine where dollars are being spent, what issues motivate restoration, and what approaches are used. By conservative estimates, in excess of $400 million has been invested in restoration projects since 1990. The majority of projects were implemented to restore forest vegetation in riparian areas and improve water quality. Although the CBW has an extremely high density of restoration activities relative to other regions of the US, only 5.4% of the project records indicated that related monitoring of project performance has occurred. To provide cost‐effective management solutions, we recommend that a centralized tracking system be developed that includes restoration projects associated with both tidal and non‐tidal waterways, along with a substantial increase in investment in the comprehensive monitoring of individual projects following implementation.